Tons emotivo-volitivos em comentários online no perfil "Quebrando o Tabu" - Lima, Edlaine Souza de (2022)
According to Bakhtin and circle, language consists of constant dialogical relationships understood in an axiological way, that is, linked to the value judgments of those involved in the communicative process. To carry out this study, the following research question is presented: what are emotional-volitional tones materialized in the online comments in the posts of the Profile Quebrando o Tabu? To answer this question, we decided to investigate concrete statements posted as comments on some posts made on The Quebrando o Tabu Profile on Instagram. To this end, a path of emotionalvolitional discourse was drawn in the light of the dialogical analysis of the discourse based on Bakhtin and the Circle, represented here in the works of Bakhtin (2011, 2012, 2013, 2015), Volóchinov (2012), among other works of scholars of theory such as the authors Brait (2005, 2006, 2014), Faraco (2009) and Francelino (2011). In view of these considerations, the general objective is to investigate, from the comments woven in four posts of the Instagram profile " Quebrando o Tabu ", which the emotionalvolitional tones can be perceived in the online comments and show how they build the axiological positioning of the enunciating subjects. This research is classified as qualitative, interpretive, bibliographic and documentary. Four instagram posts about political discourse aimed at combating the covid-19 pandemic in Brazil were selected as corpus. Thus, it is revealed the importance of perceiving the emotional-volitional tones in the specific online comments, in order to better understand the express message. It was concluded, then, that analyzing the emotional-volitional tones in the online comments of the subjects determines the construction of the meanings present in their discourses and that linguistic choices designate valorization to utterances. Thus, it was possible to observe emotional-volitional tones of incitement, order, ignorance, aggressiveness, sarcasm, seriousness and indifference. These choices also expressed the political-ideological positions expressed in the comments observed and analyzed.